Effect of Extracellular Calcium Depletion on Atrial Natriuretic Factor Secretion and Gene Expression: Calcium and ANF release - Imanshahidi, Mohsen (Iranian Journal of Pharmaceutical Sciences, 2006)
Extracellular Ca2+ concentration ([Ca2+]o) may be one of the factors affecting atrial natriuretic factor (ANF) release. In the previous studies, there are opposite reports about the effect of [Ca2+]o on ANF secretion. Therefore, the effect of [Ca2+]o depletion on ANF secretion and gene expression was studied in the present research. Isolated right atria from rats were perfused for 6 and 2 hours in the presence and absence of [Ca2+]o, and ANF secretion were measured using radioimmunoassay method. Cyclohexamide was used in another group as a protein synthesis inhibitor. ANF mRNA level in atria measured by Real time PCR. [Ca2+]o depletion induced a significant increase in basal ANF release. This stimulatory effect peaked at 2 h, then started to decrease and reached around basal levels by 6 h. Protein synthesis inhibition by cyclohexamide did not abolish or significantly decrease the stimulatory effect of Ca2+-free media on ANF secretion. The ANF gene expression was not significantly affected by Ca2+-free media. These results suggest that the contractile and endocrine function of atrial cardiocytes are differently affected by [Ca2+]o and may represent an adaptation to the dual roles of the atrial myocytes contraction and secretion.